Detection rates of colorectal neoplasia during colonoscopies and their associated factors in the SCREESCO study. Issue 11 (9th September 2022) - Sekiguchi, Masau; Westerberg, Marcus; Ekbom, Anders; Hultcrantz, Rolf; Forsberg, Anna
Abstract: Background and Aim: Colonoscopy quality, including lesion detectability, is variable, and factors influencing lesion detection are not fully understood. This study investigated lesion detection rates during colonoscopies and the associated factors in the SCREEning of Swedish COlons (SCREESCO) study. Methods: In this cross‐sectional analysis of data from SCREESCO, a large‐scale randomized controlled trial of colorectal cancer screening in the Swedish population aged 60 years, we assessed data of first‐time colonoscopies performed in both colonoscopy and fecal immunochemical test (FIT) arms. Results: This study included 16 552 individuals. The adenoma detection rate was 23.9% and 37.8% in colonoscopy and FIT arms, respectively. Regarding colonoscopy procedures, a withdrawal time ≥ 6 min was associated with higher detection rates of advanced adenomas (adjusted odds ratio [AOR] 2.474, 95% confidence interval [CI] 1.295–4.723), adenomas (2.181, 1.515–3.140), and proximal serrated lesions (pSLs) (1.713, 1.007–2.915). Antispasmodic use was associated with higher detection rates of these lesions and sessile serrated lesions (SSLs) (AOR, 95% CI: 1.523, 1.295–1.791; 1.361, 1.217–1.522; 1.450, 1.247–1.687; and 1.810, 1.512–2.167, respectively). Insertion time > 20 min was related to lower detection rates of adenomas, pSLs, and SSLs (AOR, 95% CI: 0.753, 0.639–0.887; 0.640, 0.495–0.828; and 0.704, 0.518–0.955, respectively). The relationship between a recent period and higher detection rates of pSLs and SSLs was also demonstrated. Conclusion: Lesion detectability in SCREESCO was mostly acceptable with room for improvement. In addition to sufficient withdrawal time, antispasmodic use and acquiring skills enabling short insertion time may improve lesion detection. Trial registration: ClinicalTrials.gov, ID: NCT02078804.